DOCK8 deficiency in a boy who presented with a giant aortic aneurysm between aortic root and iliac bifurcation - Türkan Patıroğlu; Himmet Haluk Akar; Mehmet Sait Doğan; Kazım Üzüm (KARE Publishing, 2016)
Summary- Dedicator of cytokinesis 8 protein (DOCK8) deficiency is an autosomal recessive, inherited form of hyper-immunoglobulin E (hyper-IgE) syndrome, characterized by persistent cutaneous viral infections, elevated IgE, eosinophilia, and allergic manifestations. The case of a 10-year-old boy who presented with giant aortic aneurysm between the aortic root and iliac bifurcation is described in the present report. Aortic aneurysm of this size has not yet been reported.